CCL19 and CCL21 modulate the inflammatory milieu in atherosclerotic lesions - Akhavanpoor, Mohammadreza; Gleißner, Christian A.; Gorbatsch, Stephanie; Dösch, Andreas; Akhavanpoor, Hamidreza; Wangler, Susanne; Jahn, Frederik; Lasitschka, Felix; Katus, Hugo; Erbel, Christian (Drug design, development and therapy, 2014)
CCL19 and CCL21 modulate the inflammatory milieu in atherosclerotic lesions Mohammadreza Akhavanpoor,1,2,* Christian A Gleissner,1,2,* Stephanie Gorbatsch,1,2 Andreas O Doesch,1,2 Hamidreza Akhavanpoor,1,2 Susanne Wangler,1,2 Frederik Jahn,1,2 Felix Lasitschka,3 Hugo A Katus,1,2 Christian Erbel1,2 1Department of Cardiology, University of Heidelberg, 2DZHK (German Centre for Cardiovascular Research), partner site Heidelberg/Mannheim, 3Institute of Pathology, University of Heidelberg, Germany *These authors contributed equally to this work Abstract: Despite advances in the pharmacologic and interventional treatment of coronary artery disease, atherosclerosis remains the leading cause of death worldwide. Atherosclerosis is a chronic inflammatory disease, and elevated expression of CCL19 and CCL21 has been observed in ruptured lesions of coronary arteries of patients with myocardial infarction and carotid plaques of patients with ischemic symptoms, as well as in plasma of coronary artery disease patients. However, the exact role of CCL19 and CCL21 in atherosclerosis remains unknown. In order to identify CCL19 and CCL21 as a novel therapeutic target, we performed bone marrow transplantation as an immunomodulatory treatment concept. Bone marrow of plt/plt mice (lacking CCL19 and CCL21-Ser) was transplanted into atherogenic Ldlr-/- mice. The study demonstrated a significantly increased inflammatory cellular infiltration into the lesions of plt/plt/Ldlr-/- mice versus controls. Although the level of chemoattraction was increased, messenger ribonucleic acid and protein levels in thoracic aorta and serum of several proinflammatory cytokines (TNFα, IFNγ, IL-6, IL-12, and IL-17) were significantly reduced in plt/plt/Ldlr-/- versus control mice. Increased influx, accompanied by reduced activation of leukocytes in atherosclerotic lesion, was accompanied by increased plaque stability but unchanged lesion development. In conclusion, modulation of the chemokines CCL19 and CCL21 represents a potent immunoregulatory treatment approach, and thus represents a novel therapeutic target to stabilize atherosclerotic lesions. Keywords: atherosclerosis, chemokines, immunomodulatory therapy, bone marrow transplantation
Gesehen am 09.11.2020